Sexual function outcomes following fracture of the penis - Nason, Gregory J. (Canadian Medical Association, 2013)
INTRODUCTION: Fracture of the penis is a rare urological emergency which occurs as a result of abrupt trauma to an erect penis. There is paucity of data regarding long-term sexual function or erectile potency following fracture of the penis. The aim of this study is to objectively assess the overall sexual function following fracture of the penis. METHODS: A retrospective analysis of 21 penile fractures was performed. A voluntary telephone questionnaire was performed to assess long term outcomes using three validated questionnaires-the Erection Hardness Grading Scale, the International Index of Erectile Function (IIEF-5) and the Brief Male Sexual Function inventory (BMSFI). RESULTS: The mean age was 33.1 years (range: 19–63). The median follow up was 46 months (range: 3–144). All fractures were a result of sexual misadventure and all were surgically repaired. There were two concomitant urethral injuries. Seventeen patients were contactable. Fourteen patients demonstrated no evidence of erectile dysfunction (ED) (IIEF-5>22), 1 patient reported symptoms of mild ED (IIEF-5, 17–21) and one patient reported mild to moderate ED (IIEF-5, 12–16). No patients reported insufficient erection for penetration (EHGS: 1 or 2). Regarding the overall BMSFI, 13 (83%) patients were mostly satisfied or very satisfied with their sex life within the previous month. CONCLUSION: In a small surgical series of men with penile fracture managed within a short time frame from presentation, we demonstrate erectile potency is maintained. Long-term overall sexual satisfaction is promising.